2016
DOI: 10.1590/1517-869220162206134684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diurnal and Nocturnal Strenuous Exercise on Serum Melatonin Levels

Abstract: Introduction: There are reports of a possible relationship between melatonin, a hormone secreted by the pineal gland, and exercise. Objective: The present study aims to investigate how diurnal and nocturnal strenuous exercise affects melatonin levels. Methods: The study enrolled 10 healthy sedentary males who did not actively exercise. The subjects had a mean age of 22.20±0.24 years, a mean height of 174.60±2.33 cm, and a mean weight of 69.70±2.42 kg. Two blood samples were collected from the subjects, one at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The studies varied in many respects, as exercise duration (short time-from 1 to 8 days, long-lasting-from 2 to 12 months), exercise type, exercise intensity (moderate, moderate-to-vigorous, acute until exhaustion), training conditions (hypoxic, normoxic conditions, indoor training, outdoor training), sex, and measuring the timing of maximal secretion of MT as well as the measurement methods. An increase of MT concentration following PE in the morning [ 90 ] and in hypoxic conditions [ 91 ], decreases in the same [ 79 , 92 ], and a lack of the effect [ 93 , 94 ] were reported. Referring to the MT measurement timing, Carlson et al [ 90 ] observed that exercise performed in the morning resulted in elevated MT secretion by 20% compared to the hormone secretion induced by the afternoon exercise.…”
Section: Physical Exercise and Melatoninmentioning
confidence: 99%
“…The studies varied in many respects, as exercise duration (short time-from 1 to 8 days, long-lasting-from 2 to 12 months), exercise type, exercise intensity (moderate, moderate-to-vigorous, acute until exhaustion), training conditions (hypoxic, normoxic conditions, indoor training, outdoor training), sex, and measuring the timing of maximal secretion of MT as well as the measurement methods. An increase of MT concentration following PE in the morning [ 90 ] and in hypoxic conditions [ 91 ], decreases in the same [ 79 , 92 ], and a lack of the effect [ 93 , 94 ] were reported. Referring to the MT measurement timing, Carlson et al [ 90 ] observed that exercise performed in the morning resulted in elevated MT secretion by 20% compared to the hormone secretion induced by the afternoon exercise.…”
Section: Physical Exercise and Melatoninmentioning
confidence: 99%